THE INFLUENCE OF RETURN ON EQUITY, SALES GROWTH AND DEBT TO EQUITY RATIO ON STOCK PRICES IN PHARMACY COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE DURING THE PANDEMIC PERIOD 2019-2021 - Irna Adistriana; Didin Fatihudin; Nurullaili Mauliddah (P3I UMSurabaya, 2024)
This research is entitled the effect of Return On Equity, Sales Growth and Debt to Equity Ratio, on share prices in pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) during the pandemic period 2019-2021. There are 7 samples with the research sampling method using purposive sampling technique. This research analysis uses the Static Package for the Social Sciences (SPSS 26) program. The results of this research partially show that Return On Equity and Debt to Equity Ratio have a significant effect on stock prices, while Sales Growth does not have a significant effect on stock prices. Simultaneously, the results of Return On Equity, Sales Growth and Debt to Equity Ratio simultaneously and significantly influence stock prices.